An index of efficiency for the Athens Stock Exchange - Δριτσάκης, Νικόλαος; Κάπαρης, Αναστάσιος; Τζιλιλής, Δημήτριος (SPOUDAI Journal of Economics and Business, 2003)
This paper attempts to construct a new more efficient index, which examines the behaviour of stock return in the Athens Stock Exchange, the market efficiency in evaluating equity and finally the relation between returns and volatility. Using daily data from January 1990 until December 1999, we examine the index of all the public quoted companies in the Athens Stock Exchange. The data were collected from the Imperial College database. The models estimated are a special case of the Generalised Autoregressive Conditional Heteroscedasticity (GARCH) family; more specifically the GARCH (p,q)-M. JEL classification: G14